Narratives of solidarity: experimental evidence on shifting attitudes towards refugees. - Yabanci, Bilge; Elçi, Ezgi (Journal of Ethnic & Migration Studies, 2026)
This study investigates the constitutive role of narratives – multilayered, story-like, normative communications – in shaping public attitudes towards one of the world's most systematically stigmatised groups: forcibly displaced migrants such as refugees, asylum seekers, and undocumented migrants. We introduce a novel sequential design where qualitative fieldwork informs the development of a large-scale online survey experiment (N = 1507). Our work tests the impact of solidarity-driven and bias-disrupting narratives in Turkey, a critical host country for refugees over the last decade, amidst intense public hostility, departing from experimental scholarship's common focus on negative narratives that highlight the outsider status of migrants. We demonstrate that even brief exposure to our narratives significantly improves both attitudinal solidarity and the willingness to take pro-refugee action in a challenging context. Critically, these effects are most pronounced among religious individuals, lower-income groups, and people who have minimal or no contact with refugees previously. These results provide strong evidence that carefully crafted narratives can shift public opinion and change the attitudes of some key groups towards refugees who are reported to hold firm anti-refugee and anti-migrant views. Overall, the study provides empirically grounded strategies for countering the pervasive narrative dominance of nativist actors who rely on sensationalised and misleading narratives.